2001
DOI: 10.1073/pnas.151239698
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule spectroscopy of the β 2 adrenergic receptor: Observation of conformational substates in a membrane protein

Abstract: Single-molecule studies of the conformations of the intact ␤2 adrenergic receptor were performed in solution. Photon bursts from the fluorescently tagged adrenergic receptor in a micelle were recorded. A photon-burst algorithm and a Poisson time filter were implemented to characterize single molecules diffusing across the probe volume of a confocal microscope. The effects of molecular diffusion and photon number fluctuations were deconvoluted by assuming that Poisson distributions characterize the molecular oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 21 publications
3
73
1
Order By: Relevance
“…In rhodopsin, for example, the existence of multiple conformers is evident from absorbance changes (9). Multiple receptor conformational states are also evident in single molecule spectroscopy studies of the ␤2-adrenergic receptor (11) and are supported by the presence of phenotypically different serotonin 5HT2C receptor activation mutants (12). Pharmacological evidence for signal trafficking has been reported in several heptahelical receptors (14,15,66,67).…”
Section: Translocation and Phosphorylation Of Akt By D 2 Receptormentioning
confidence: 87%
“…In rhodopsin, for example, the existence of multiple conformers is evident from absorbance changes (9). Multiple receptor conformational states are also evident in single molecule spectroscopy studies of the ␤2-adrenergic receptor (11) and are supported by the presence of phenotypically different serotonin 5HT2C receptor activation mutants (12). Pharmacological evidence for signal trafficking has been reported in several heptahelical receptors (14,15,66,67).…”
Section: Translocation and Phosphorylation Of Akt By D 2 Receptormentioning
confidence: 87%
“…Activation occurs by transition through intermediate conformations (38), with the equilibrium between these forms showing a characteristic pH sensitivity (39). The existence of multiple receptor conformers is also evident in single molecule spectroscopy studies of the ␤ adrenergic receptor (40). Pharmacological studies suggest that the existence of distinct receptor conformers can have functional significance.…”
mentioning
confidence: 99%
“…Indeed, many reports point at a model where GPCRs are highly dynamic proteins capable of adopting a large number of conformational states that signal with different efficacies to various pathways (3). The most detailed description of the conformational repertoire that a GPCR can adopt has been obtained in the case of the β 2 -adrenergic receptor with an experimental demonstration of a complex conformational landscape where ligands with distinct pharmacological properties shift the conformation of the receptor from one state to another (4)(5)(6)(7)(8)(9)(10)(11). In the same way, we showed that ligands with different efficacies stabilize different conformations of the serotonin receptor (12).…”
mentioning
confidence: 99%